Math Problem Statement

Without using truth table prove that

neg[[(p v q)^ r] implies neg q] iff q ^ r

Solution

To prove the equivalence ¬[(pq)r]¬q    qr\neg[(p \vee q) \land r] \rightarrow \neg q \iff q \land r without using a truth table, we'll approach the problem using logical equivalences and reasoning.

Step 1: Analyze the left-hand side (LHS)

The expression on the left-hand side is: ¬[(pq)r]¬q\neg[(p \vee q) \land r] \rightarrow \neg q

Let's break it down:

  1. Negate the conjunction: ¬[(pq)r]¬(pq)¬r\neg[(p \vee q) \land r] \equiv \neg(p \vee q) \vee \neg r This uses De Morgan's law: ¬(AB)¬A¬B\neg(A \land B) \equiv \neg A \vee \neg B.

  2. Negate the disjunction pqp \vee q: ¬(pq)¬p¬q\neg(p \vee q) \equiv \neg p \land \neg q Again, using De Morgan's law: ¬(AB)¬A¬B\neg(A \vee B) \equiv \neg A \land \neg B.

So the expression becomes: ¬[(pq)r](¬p¬q)¬r\neg[(p \vee q) \land r] \equiv (\neg p \land \neg q) \vee \neg r

Thus, the LHS can be rewritten as: [(¬p¬q)¬r]¬q[(\neg p \land \neg q) \vee \neg r] \rightarrow \neg q

Step 2: Simplify the implication

Recall the logical implication ABA \rightarrow B is equivalent to ¬AB\neg A \vee B. So, the LHS becomes: ¬[(¬p¬q)¬r]¬q\neg[(\neg p \land \neg q) \vee \neg r] \vee \neg q

Let's simplify ¬[(¬p¬q)¬r]\neg[(\neg p \land \neg q) \vee \neg r]:

  • ¬[(¬p¬q)¬r]\neg[(\neg p \land \neg q) \vee \neg r] can be written as ¬(¬p¬q)¬(¬r)\neg(\neg p \land \neg q) \land \neg(\neg r).

Thus: (¬(¬p¬q)¬(¬r))¬q(\neg(\neg p \land \neg q) \land \neg(\neg r)) \vee \neg q

Simplifying further using De Morgan's law: (pq)r¬q(p \vee q) \land r \vee \neg q

Since r¬qr \vee \neg q can be true if qrq \land r is false, the expression reduces to: ¬q¬r¬q¬qr\neg q \vee \neg r \vee \neg q \equiv \neg q \vee r

Now the entire LHS implication reduces to: ¬qrr\neg q \vee r \equiv r

Step 3: Compare with the right-hand side (RHS)

The RHS is qrq \land r.

To satisfy the equivalence ¬qr    qr\neg q \vee r \iff q \land r:

  • If qrq \land r is true, rr must be true, and (\neg q\